Analysis of lithium-ion indirect liquid cooling battery thermal management system with high discharge rate - Nizam, Muhammad; Putra, Mufti Reza Aulia (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Electric vehicles are developing rapidly and require technological support. Electric vehicles require good power storage. One of the reasonable parameters of a battery pack is its high discharge capability. A high discharge rate requires suitable cell and heat management capabilities in the battery pack. When discharging, it produces heat energy and needs to be released. The battery thermal management system (BTMS) is a method used to maintain battery heat. BTMS using liquid has a better performance compared to phase-change memory (PCM) and air cooling. The use of liquid coolers still has limitations. Namely, the weight of the cooling system is quite large because of a large amount of liquid which increases the weight of the battery. This study offers the potential to use mini channels mounted on cooling plates for application as BTMS. This research used the finite element method (FEM) process by simulating the process of fluid flow that occurs when the battery is used at various C rates. The results of this study indicate that the type of BTMS can keep the battery hot at working temperatures below 40 ºC.